2018
DOI: 10.1111/tpj.13844
|View full text |Cite
|
Sign up to set email alerts
|

Identification and functional study of the endoplasmic reticulum stress sensor IRE1 in Chlamydomonas reinhardtii

Abstract: In many eukaryotes, endoplasmic reticulum (ER) stress activates the unfolded protein response (UPR) via the transmembrane endoribonuclease IRE1 to maintain ER homeostasis. The ER stress response in microalgae has not been studied in detail. Here, we identified Chlamydomonas reinhardtii IRE1 (CrIRE1) and characterized two independent knock-down alleles of this gene. CrIRE1 is similar to IRE1s identified in budding yeast, plants, and humans, in terms of conserved domains, but differs in having the tandem zinc-fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 54 publications
2
19
0
Order By: Relevance
“…Cultures were sampled at 24, 48 and 72 hr to take photographs and measure total chlorophyll concentration. ire1 cells were used as a positive control given the essential role of the Ire1 kinase in the activation of the erUPR (Yamaoka et al, 2018). ( B ) Histograms of total chlorophyll concentrations (µg/ml) measured from TAP liquid cultures collected during the experiment described in Figure 4—figure supplement 2A.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cultures were sampled at 24, 48 and 72 hr to take photographs and measure total chlorophyll concentration. ire1 cells were used as a positive control given the essential role of the Ire1 kinase in the activation of the erUPR (Yamaoka et al, 2018). ( B ) Histograms of total chlorophyll concentrations (µg/ml) measured from TAP liquid cultures collected during the experiment described in Figure 4—figure supplement 2A.…”
Section: Resultsmentioning
confidence: 99%
“…mars1 cells proved remarkably more sensitive than WT to metronidazole in photoheterotrophic and in phototrophic conditions, while their growth was not affected when grown in the dark (Figure 4C, Figure 4—figure supplement 1B–F). By contrast, WT and mars1 cells were equally sensitive to tunicamycin, a chemical inducer of proteotoxic stress in the ER (Figure 4—figure supplement 2A–C) (Yamaoka et al, 2018). Moreover, as we observed for other conditions inducing the cpUPR, the metronidazole-mediated activation of cpUPR target genes, such as VIPP2 and HSP22E/F, was dependent on Mars1 and its kinase activity (Figure 4D).…”
Section: Resultsmentioning
confidence: 99%
“…The plant IRE1 as well as the availability of bZIP28 and bZIP60 together are strictly necessary to overcome temporary and prolonged stress, as demonstrated by the evidence that death is accelerated in the ire1a ire1b and bzip60 bzip28 mutants compared to WT in situations of recovery from temporary ER stress or in conditions of chronic ER stress ((Nagashima et al 2011, Chen et al 2012, Deng et al 2013, Liu et al 2016a); Figures 4, 5). An analysis of ER stress response in Chlamydomonas reinhardtii reported a significant transcriptional induction of ROS-dependent marker genes in IRE1 knockouts (Yamaoka et al 2018). These findings led to the hypothesis that an increase in ROS may contribute to the ER stress sensitivity of ire1 knockout lines in this model systems (Yamaoka et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…An analysis of ER stress response in Chlamydomonas reinhardtii reported a significant transcriptional induction of ROS-dependent marker genes in IRE1 knockouts (Yamaoka et al 2018). These findings led to the hypothesis that an increase in ROS may contribute to the ER stress sensitivity of ire1 knockout lines in this model systems (Yamaoka et al 2018). Our results that in the Arabidopsis ire1a ire1b line, which is hypersensitive to ER stress ((Chen et al 2012); Figures 4–6), the H 2 O 2 levels are higher at 24 and 48 hours of Tm treatment compared to WT (Figure 2E) corroborate this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Somewhat more difficult to explain are the findings of Yamaoka et al (2018) who found that treatment of C. reinhardti with the endoplasmic reticulum stress agents, tunicamycin, induces the expression of the resident chaperones binding protein 1 ( BIP1 ) and calreticulin 2 ( CAL2 ). These genes are reliable UPR biomarkers and their upregulation is usually taken to indicate an activation of a canonical UPR transcription response.…”
Section: Introductionmentioning
confidence: 99%